Optimalisasi Edukasi Pencegahan Stunting melalui Program Sosialisasi Partisipatif di Desa Kemuning, Kabupaten Tangerang - Wahyudi, Tri; Ika Arinia Indriyany; Nana Nofianti; Hendrawan Syafrie; Diqbal Satyanegara; Titania Mukti; Nufus Kanani (Ikatan Cendekiawan Muda Akuntansi, 2025)
Stunting remains a significant public health issue in Indonesia, particularly in rural areas. Desa Kemuning is one of the regions with a high prevalence of stunting that requires special attention. This community service activity aims to optimize stunting prevention education through a participatory socialization program involving various stakeholders, including local communities, health cadres, and village officials. The methods used include community-based active participation and focused discussions to enhance understanding, engagement, and collective commitment to preventing stunting. This activity successfully reached 50 participants, consisting of pregnant women and children in Desa Kemuning. The materials presented covered the importance of balanced nutrition, parenting practices, and environmental sanitation to support optimal child growth. The program demonstrated that a participatory approach in socialization effectively improves community understanding and awareness of stunting prevention. By involving various parties, it is hoped that the sustainability of this effort will have a significant positive impact on reducing stunting rates in Desa Kemuning.